The Impact of Different Hepatitis B Virus Serological Statuses on the Safety of Different Chemotherapy Regimens in Female Breast Cancer Patients: A Within-Subject Longitudinal Study - Li, Zhao-Xing; Liu, Dong-Li; Hu, Lei; Peng, Bai-Qing; Qu, Xiu-Quan; Mu, Li-Yuan; Cheng, Xiao-Chun; Qiu, Pu; Huang, Yu-Xuan; Li, Xi-Rui; Kong, Ling-Quan (Cancers, 2025)
Background: Breast cancer patients with hepatitis B virus (HBV) infection or past HBV infection face heightened risks of chemotherapy-induced hepatotoxicity and HBV reactivation (HBVr). This study aims to evaluate the impact of different HBV serological statuses on the safety of chemotherapy regimens based on paclitaxel throughout the treatment cycle. Methods: This retrospective cohort study analyzed 4562 female breast cancer patients, categorized into three groups: 366 with HBV infection (HBsAg+), 2529 with past HBV infection (HBsAg−/HBcAb+), and 1667 without HBV infection (control group). The Primary events included liver injury, HBVr, treatment interruption, and laboratory indicator evaluation. Demographic characteristics and periodic laboratory parameters were recorded for within-subject longitudinal analysis. Results: Before chemotherapy, the incidence of liver injury was highest in the HBV-infected group (18.2%), intermediate in the past-infection group (13.2%), and lowest in the control group (12.0%). Throughout chemotherapy, the cumulative incidence of liver injury remained highest in the HBV-infected group (83.2%), compared to the past-infection (71.2%) and control (70.9%) groups. Chemotherapy interruption rates followed a similar gradient: 12.4% in the HBV-infected group, 6.9% in the past-infection group, and 5.5% in the control group. HBV-infected patients had a significantly higher risk of hepatotoxicity than controls during cycle 4 (relative risk 1.56, 95% CI 1.06 to 2.29) and cycle 5 (1.28, 1.09 to 1.75). HBVr occurred in 13 patients with HBV-infected. Conclusions: HBV serological status significantly impacts chemotherapy safety and treatment interruption. Prophylactic antiviral therapy and intensified monitoring during high-risk cycles (cycle 4 and cycle 5) are critical. These findings underscore the necessity of stratified management for HBV-affected breast cancer patients during chemotherapy.